2020
DOI: 10.1097/md.0000000000023088
|View full text |Cite
|
Sign up to set email alerts
|

A study of 18F-FLT positron emission tomography/computed tomography imaging in cases of prefibrotic/early primary myelofibrosis and essential thrombocythemia

Abstract: The objectives of this research project are to study in patients with primary myelofibrosis (PMF) and Essential Thrombocythemia (ET); (1) the uptake patterns of 18 FLT-PET (FLT-PET) and its value in diagnosing, staging, and treatment response monitoring of malignant hematopoiesis, (2) compare imaging findings from FLT-PET with bone marrow biopsy (standard of care), and (3) associate FLT-PET uptake patterns with genetic makeup such as JAK2 (Janus kinase 2), CALR (Calreticulin), MPL (myelo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 6 publications
(5 reference statements)
0
10
0
Order By: Relevance
“…The objective of this study is to explore the diagnostic value of FLT-PET in malignant hematopoiesis of Pre-PMF and ET. The potential to use FLT-PET metrics to differentiate between Pre-PMF and ET is assessed 3 since this differentiation will optimize the therapeutic interventions (eg, anti-platelets and anti-coagulants) as thrombosis is related to ET while hemorrhage is more associated with pre-PMF.…”
Section: Introductionmentioning
confidence: 99%
“…The objective of this study is to explore the diagnostic value of FLT-PET in malignant hematopoiesis of Pre-PMF and ET. The potential to use FLT-PET metrics to differentiate between Pre-PMF and ET is assessed 3 since this differentiation will optimize the therapeutic interventions (eg, anti-platelets and anti-coagulants) as thrombosis is related to ET while hemorrhage is more associated with pre-PMF.…”
Section: Introductionmentioning
confidence: 99%
“…It has heterogeneous clinical presentation that varies from isolated thrombocytosis, similar to ET, up to symptoms of high-risk PMF. Retrospective studies showed that survival of patients with pre-PMF is worse than that of ET and better than overt PMF [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…MG is a recognized paraneoplastic syndrome in patients with thymoma (~15% of MG patients) [7], secondary to AChR/MuSK antibodies' production from the thymic source. Only 31% had thymoma in our cohort, whereas 77% had positive AChR/ MuSK antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…2016 WHO category of MPNs includes the three major subcategories of Janus kinase 2 (JAK2)/ calreticulin (CALR)/ myeloproliferative leukemia virus oncogene (MPL) mutation-related MPNs: Polycythemia Vera (PV), Essential Thrombocythemia (ET), and Primary Myelofibrosis (PMF), as well as four other clinic-pathologic entities: chronic myeloid leukemia (CML), chronic neutrophilic leukemia (CNL), chronic eosinophilic leukemia, not otherwise specified (CEL-NOS) and MPN, unclassifiable (MPN-U) [6]. PMF includes pre-fibrotic/early PMF (pre-PMF) as well [7]. The diagnostic hallmark of CML is the invariable presence of the BCR-ABL1 mutation [6,8,9].…”
Section: Introductionmentioning
confidence: 99%